Benchmarking for strategic regional metropolitan plans - Darley, Mary (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2003)
There are approximately 120 metropolitan regions and areas, with populations over 500,000, in the European Union, non-EU and Central and Eastern European Countries (CEEC). METREX is a Network of practilioners - that is. politicians, officia)s and their advisers with a common interest in spalial planning and development at the metropolitan level. The Network has a twin purpose: ?_? to promote the exchange of knowledge between practitioners on strategic issues of common interest. ?_? to contribute the metropolitan dimension to planning at the European level. In 1999 METREX and the Junta Mctropolitana do Pono, with the support of the European Commission, convened the Porto Convocation of European metropolitan regions and areas. An outcome was the Porto Metropolitan Magna Carta and its associated Practice Benchmark. Over 40 European metropolitan areas signed the Metropolitan Magna Carta of Spatial Planning and Development Intent and areas and the partners confirmed a common intention to: ?_? Pursue the aim of effective spatial planning and development at the metropolitan level in Europe, by promoting the necessary competence, capability and process
Papers from practice
Keywords: Urban geography -- Ireland